Effectiveness of Health Promotion Intervention on Smoking Behavior Prevention and Its Impact on Nutritional Status in South Sulawesi Community: A Literature Review - Nur Afiaty Mursalim; Puspita Dewi (CV. Global Health Publication, 2026)
Background: Smoking behavior is one of the leading risk factors for non-communicable diseases and has a significant impact on individual and community nutritional status. In South Sulawesi, the prevalence of active smokers remains high, particularly among the productive age group. Evidence-based health promotion interventions are necessary to reduce this prevalence while simultaneously improving community nutrition. Aims: This study aimed to analyze the effectiveness of various health promotion intervention approaches in preventing smoking behavior and to evaluate their impact on the nutritional status of communities in South Sulawesi. Methods: A descriptive-analytical literature review was conducted using articles published between 2016 and 2025 from PubMed, Scopus, ScienceDirect, Google Scholar, and Garuda databases. The selection process followed PRISMA guidelines. A total of 14 studies met the inclusion criteria and were analyzed using thematic synthesis. Results: Health promotion interventions such as motivational interviewing-based counseling, group education, and social media campaigns were proven to significantly reduce the prevalence of smoking behavior. Reduction in smoking behavior positively correlated with improvements in nutritional status, indicated by increased intake of essential nutrients and reduced risk of stunting and micronutrient deficiencies in target populations. Conclusions: Integrated and community-participation-based health promotion approaches were proven effective in preventing smoking behavior and contribute to improving nutritional status in South Sulawesi communities. Integration of these interventions into regional health programs is strongly recommended.